Assessment of early orthodontic treatment needs in children aged 4-6 using the baby-risk of malocclusion assessment (Baby-ROMA) index - Yilmaz, Neslihan; Acar; Elif Gokce Erkan; Aydin, Elif Gul; Tugutlu, Esra Ceren (Journal of Pedodontics, 2026)
Background: This study aimed to assess the prevalence of malocclusion and orthodontic treatment needs using the Baby-ROMA index in a group of Turkish children aged 4–6 years, and to examine the association between Baby-ROMA index scores and demographic and dental characteristics.
Methods: A total of 203 children aged 4–6 years with primary dentition and no previous orthodontic treatment were included. Demographic data and parental perceptions of orthodontic treatment need were collected via interviews. Clinical examinations were performed using the Baby-ROMA index, and dental caries status was assessed using the decayed, missing and filled teeth (dmft) index. The presence of primate spaces, molar relationships, and canine relationships were also recorded.
Results: The most prevalent risk factors for malocclusion were parafunctional habits (27.6%), poor oral hygiene (27.1%), and dental caries or early loss of primary teeth (25.1%). The results indicated statistically significant differences in Baby-ROMA index scores based on age groups (p = 0.004), right molar relationship (p = 0.019) and dmft scores (p < 0.001). Despite these findings, 76.2% of parents did not perceive any orthodontic treatment need for their children.
Conclusions: Our findings demonstrate a high prevalence of malocclusion risk and orthodontic treatment needs among Turkish children aged 4–6 years. The results highlight the importance of early intervention and preventive strategies to address key risk factors, such as parafunctional habits, dental caries and poor oral hygiene.